Recombinant Toxin Fragments - SUTTON J. MARK; WAYNE JONATHAN; FOSTER KEITH ALAN; QUINN CONRAD PADRAIG; STANCOMBE PATRICK; SHONE CHARLES CLIFFORD; CHADDOCK JOHN; MARKS PHILIP (2009)
Antigenic compositions are provided comprising a single chain polypeptide comprising first and second domains, wherein said first domain is a clostridial neurotoxin light chain or a fragment or a variant thereof and is capable of cleaving one or more vesicle or plasma membrane associated proteins essential to exocytosis; and said second domain is a clostridial neurotoxin heavy chain HN portion or a fragment or a variant thereof, wherein said second domain is capable of (i) translocating the polypeptide into a cell or (ii) increasing the solubility of the polypeptide compared to the solubility of the first domain on its own or (iii) both translocating the polypeptide into a cell and increasing the solubility of the polypeptide compared to the solubility of the first domain on its own; and wherein the second domain lacks a functional C-terminal part of a clostridial neurotoxin heavy chain designated HC thereby rendering the polypeptide incapable of binding to cell surface receptors that are the natural cell surface receptors to which native clostridial neurotoxin binds. Antibodies that bind to the polypeptides, and compositions comprising these antibodies, are also provided, as are DNA vaccines comprising polynucleotides that encode these polypeptides. The antigenic and antibody compositions, and the DNA vaccine compositions, can be used in methods of immunising against, or treating, clostridial neurotoxin poisoning in a subject by administering to that subject a therapeutically effective amount of the composition.